(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the history of Bukhara Radio’s activities, recent news from the broadcast schedule, newspaper reviews, concert programs broadcasted through gramophone records, literary broadcasts, and programs intended for children. It analyzes how technical advancements are gradually expanding opportunities in the field.